Development of a method for assessing the immunological reactivity of the animal body to prevent the development of pathology in the early stages of postnatal development - Agarkov Alexander; Gorchakov Edward; Agarkov Nikolay; Fedota Natalia; Tsygansky Roman (E3S Web of Conferences, 2021)
The study of immunological relationships in the functional system “mother-placenta-offspring” can make a significant contribution to the solution of the issue of improving the safety of the population of newborn animals and poultry. The pathology of the antenatal development of animals has not been sufficiently studied. Antenatal pathology of animals is more often manifested in the form of congenital malformations (anomalies) of development. Congenital defects are usually called those that occur during intrauterine development. However, congenital malformations are also observed in the period of postnatal development – as a consequence of a violation of the further formation of organs in animals. There is a need to develop a method for determining the immunological reactivity of the animal body, which would allow to assess the combined functional state of cell-mediated immunological reactivity of innate and acquired immunity in the functional system “mother-placenta-offspring” and determine the factors that cause immunosuppression. Determination of the immunological reactivity of the animal body includes a blood test by conducting a biological test, which uses the biological activity of red blood cells in the Nitroblue Tetrazolium Test and according to their sorption activity-more than 40% - animals are classified as individuals with reduced immunological reactivity among similar ones.